Psychological Dimensions of Organizational Culture in Healthcare Institutions - Sasa Stepanovic; Branka Radojevic; Ana Grbic (Journal Human Research in Rehabilitation, 2026)
Organizational culture represents a complex system of shared values, professional beliefs, and behavioral patterns that shape employees’ cooperation, decision-making, and work performance within healthcare institutions. The quality of organizational culture directly influences employees’ motivation, job satisfaction, and readiness to accept changes in contemporary healthcare systems. This study examines the relationship between the psychological dimensions of organizational climate and employees’ innovation readiness in everyday professional practice. The research was conducted on a sample of 127 employees from different professional profiles working at the Health Center Zajecar. Data were collected using a questionnaire designed to assess organizational climate and employees’ innovation potential in healthcare institutions in Serbia. The results indicate that employees demonstrate readiness to accept new professional solutions; however, their implementation largely depends on organizational support, participative leadership, and available institutional resources. The findings highlight the importance of strengthening transformational leadership, improving internal communication, and developing organizational mechanisms that support innovation in healthcare institutions.